Macromol. Rapid Commun. 19/2017. Issue 19 (4th October 2017) - Kularatne, Ruvanthi N.; Yang, Annie; Nguyen, Hien Q.; McCandless, Gregory T.; Stefan, Mihaela C.
Abstract : Front Cover : Ziegler‐Natta (ZN) catalysts are used for the polymerization of dienes, but their inability to polymerize polar vinyl monomers limits their application in industry. As an alternative to ZN catalysts, the NdCl3 ·3TEP/TIBA catalytic system can polymerize dienes as well as polar vinyl monomers, which could eventually be beneficial to industrial applications. Further details can be found in article number1700427 by Mihaela C. Stefan* and co‐workers.